The gender gap in early career in Mongolia - Francesco Pastore (Institute for the Study of Labor (IZA), 2009)
Relatively little is known about the youth labour market in general and about gender differences in Mongolia, one of the fifty poorest countries in the world. This paper addresses the issue by taking advantage of a School to Work Survey (SWTS) on young people aged 15-29 years carried out in 2006. On average, female wages are not lower than those of males. However, women have a much higher average educational level than men: in fact, although not statistically significant among teenagers (15-19), the conditional gender gap becomes significant and sizeable for the over-20. The Juhn, Murphy and Pierce (1993) decomposition confirms that, if wages were paid equally, women should have 11.7% more considering only their educational advantage and overall 22% more, a substantial gap for the low earnings of Mongolians.
urn:nbn:de:101:1-20091019293
Keywords: I21; J13; J24; J31; J62; P30; R23; 330; School-to-work transitions; earnings equations; decomposition analysis; gender wage gap; Asia; Mongolia; Lohndifferenzierung; Berufseinstieg; Frauenbildung; Bildungsniveau; Geschlecht; Mongolei